Hybrid Antigens Expressing Surface Loops of ZnuD From Acinetobacter baumannii Is Capable of Inducing Protection Against Infection - Qamsari, Maryam Mobarak; Rasooli, Iraj; Chaudhuri, Somshukla; Astaneh, Shakiba Darvish Alipour; Schryvers, Anthony B. (Frontiers in Immunology, 2020)
Acinetobacter baumannii is an important human pathogen causing substantial mortality in hospitalized patients for which treatment with antibiotics has become problematic due to growing antibiotic resistance. In an attempt to develop alternative strategies for dealing with these serious infections surface antigens are being considered as targets for vaccines or immunotherapy. The surface receptor proteins required for zinc acquisition in Gram-negative bacterial pathogens have been proposed as vaccine targets due to their crucial role for growth in the human host. In this study we selected the putative ZnuD1 outer membrane receptor from A. baumannii as a target for vaccine development. Due to challenges in production of an integral outer membrane protein for vaccine production, we adopted a recently described hybrid antigen approach in which surface epitopes from the Neisseria meningitidis TbpA receptor protein were displayed on a derivative of the C-lobe of the surface lipoprotein TbpB, named the loopless C-lobe (LCL). A structural model for ZnuD1 was generated and four surface loops were selected for hybrid antigen production by computational approaches. Hybrid antigens were designed displaying the four selected loops (2,5,7 and 11) individually or together in a single hybrid antigen. The hybrid antigens along with ZnuD1 and the LCL scaffold were produced in the E. coli cytoplasm either as soluble antigens or as inclusion bodies, that were used to generate soluble antigens upon refolding. Mice were immunized with the hybrid antigens, ZnuD1or LCL and then used in an A. baumannii sepsis model to evaluate their ability to protect against infection. As expected, the LCL scaffold did not induce a protective immune response, enabling us to attribute observed protection to the displayed loops. Immunization with the refolded ZnuD1 protein protected 63% of the mice while immunization with hybrid antigens displaying individual loops achieved between 25 and 50% protection. Notably, the mice immunized with the hybrid antigen displaying the four loops were completely protected from infection.